Pallas's diary from the expedition to the Cheremshan River basin - A.G. Abaydulova; A.K. Salmin (Ученые записки Казанского университета: Серия Гуманитарные науки)
The part of Professor P.S. Pallas's diary describing the travel through settlements along the Cheremshan River basin as part of the expeditions of 1768–1774 has been translated for the first time. In the chronological sense, it covers the period from September to October of 1768. During that period, P.S. Pallas was wholly engaged in the research of the Tatars, Chuvashs, Mordovians, and Russians who lived in the Cheremshan River basin. The following geographical areas were described in the diary: the Novaya Malykla and Cherdakly districts of the Ulyanovsk region; Almetyevsk, Bugulma, Leninogorsk, Nurlat, and Cheremshan districts of the Republic of Tatarstan; Chelno-Vershiny and Shentala districts of the Samara region. It was during those months that P.S. Pallas collected invaluable materials on mines, useful plants, clothes, rituals, and faiths. The members of the expedition also paid attention to the landscape. For example, they noted that the lands were basically a flat steppe or croplands. Those observations were the first (and most reliable) sources where the Cheremshan River area was described.